Defining and delivering resilient ecological networks: Nature conservation in England. Issue 6 (9th July 2018) - Isaac, Nick J. B.; Brotherton, Peter N. M.; Bullock, James M.; Gregory, Richard D.; Boehning‐Gaese, Katrin; Connor, Ben; Crick, Humphrey Q. P.; Freckleton, Robert P.; Gill, Jennifer A.; Hails, Rosemary S.; Hartikainen, Minna; Hester, Alison J.; et al.
Abstract: Planning for nature conservation has increasingly emphasised the concepts of resilience and spatial networks. Although the importance of habitat networks for individual species is clear, their significance for long‐term ecological resilience and multi‐species conservation strategies is less established. Referencing spatial network theory, we describe the conceptual basis for defining and assessing a network of wildlife areas that supports species' resilience to multiple forms of perturbations and pressures. We explore actions that could enhance network resilience at a range of scales, based on ecological principles, with reference to four well‐established strategies for intervention in a spatial network ("Better, Bigger, More and Joined") from the influential Making Space for Nature report by Lawton et al. (2010 ). Building existing theory into useable and scalable approaches applicable to large numbers of species is challenging but tractable. We illustrate the policy context, describe the elements of a long‐term adaptive management plan and provide example actions, metrics and targets for early implementation using England as a case study, where there is an opportunity to include large‐scale ecological planning in a newly launched 25‐year environment plan. Policy implications . The concept of resilient ecological networks has attracted scientific and political support, but there is no consensus on what a resilient network would look like, or how to assess it. Therefore, it is unclear whether existing targets for action will be sufficient to achieve network resilience. We show that the scientific principles to place resilience and network theory at the heart of large‐scale and long‐term environmental planning are established and ready to implement in practice. Delivering a resilient network to support nature recovery is achievable and can be integrated with ongoing conservation actions and targets, by assessing their effectiveness on properties of the entire network. England's 25 Year Environment Plan promises to deliver a natural environment that is protected and enhanced for the future and so provides the ideal testbed.